Identification of patients at high risk of secondary extramedullary multiple myeloma development - Stork, Martin; Sevcikova, Sabina; Minarik, Jiri; Krhovska, Petra; Radocha, Jakub; Pospisilova, Lenka; Brozova, Lucie; Jarkovsky, Jiri; Spicka, Ivan; Straub, Jan; Pavlicek, Petr; Jungova, Alexandra; et al. (British journal of haematology, 2022)
Multiple myeloma (MM) is characterized by malignant plasma cell infiltration of the bone marrow. In extramedullary multiple myeloma (EMD), a subclone of these cells migrates out of the bone marrow. Out of 4 985 MM patients diagnosed between 2005 and 2017 in the Czech Republic, we analyzed 234 secondary EMD patients to clarify risk factors of secondary EMD development. We found younger age [<65 years; odds ratio (OR) 4·38, 95% confidence interval (CI): 2·46-7·80, P < 0·0001], high lactate dehydrogenase (LDH) levels (>5 μkat/l; OR 2·07, 95% CI: 1·51-2·84, P < 0·0001), extensive osteolytic activity (OR 2·21, 95% CI: 1·54-3·15, P < 0·001), and immunoglobulin A (IgA; OR 1·53, 95% CI: 1·11-2·11, P = 0·009) or the non-secretory type of MM (OR 2·83; 95% CI: 1·32-6·04, P = 0·007) at the time of MM diagnosis to be the main risk factors for secondary EMD development. Newly diagnosed MM (NDMM) patients with subsequent EMD had inferior median progression-free (PFS) and overall (OS) survival when compared to NDMM patients without future EMD [mPFS: 13·8 months (95% CI: 11·4-16·3) vs 18·8 months (95% CI: 17·7-19·9), P = 0·006; mOS: 26·7 months (95% CI: 18·1-35·4) vs 58·7 months (95% CI: 54·8-62·6), P < 0·001]. We found that NDMM patients with specific risk factors associated with secondary EMD development have a more aggressive disease course before secondary EMD develops.
Keywords: analýza přežití; Male; retrospektivní studie; Risk Factors; prognóza; multiple myeloma; Aged; Multiple Myeloma; mužské pohlaví; senioři; Survival Analysis; prognostic factors; lidé; ženské pohlaví; Humans; rizikové faktory; Prognosis; extramedullary disease; Retrospective Studies; mnohočetný myelom; Female